2009
DOI: 10.1002/jmri.21952
|View full text |Cite
|
Sign up to set email alerts
|

Personal exposure to static and time‐varying magnetic fields during MRI system test procedures

Abstract: Purpose: To assess personal time-weighted average (TWA) static magnetic field and time-varying magnetic field exposure for several system testing tasks routinely conducted by engineers at an MRI manufacturing plant. Materials and Methods:Personal exposure was measured using a personal dosimeter that measured B and dB/dt in all three orthogonal directions with a 1 Hz frequency. TWA exposure was calculated and random effects and linear mixed effects models were used to assess exposure levels and variability.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 15 publications
(23 reference statements)
0
24
1
Order By: Relevance
“…Total exposure to the SMF (B) was obtained in millitesla (mT) and total exposure to motioninduced TVMF (dB/dt) in mT/s. More information about the dosimeter can be found in [24][25][26]. Participants could be measured on multiple days (1 -3), and in this case, exposure was averaged across shifts as a proxy for average, typical exposure.…”
Section: Personal Exposure Measurementsmentioning
confidence: 99%
“…Total exposure to the SMF (B) was obtained in millitesla (mT) and total exposure to motioninduced TVMF (dB/dt) in mT/s. More information about the dosimeter can be found in [24][25][26]. Participants could be measured on multiple days (1 -3), and in this case, exposure was averaged across shifts as a proxy for average, typical exposure.…”
Section: Personal Exposure Measurementsmentioning
confidence: 99%
“…Recently, several magnetic field exposure measurements on personnel during MRI assembly and testing in the environment of 1.5 and 3 T magnets have been performed [10]. The magnetic field exposure of MR personnel has also been investigated in the environment of MR systems up to 4 T [4,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on occupational exposures in MRI units with 1-3 T scanners reported that exposures induced by movements in SMF may be above threshold values derived from both ICNIRP and the Institute of Electrical and Electronics Engineers (IEEE) for the 0-7 Hz frequency range. [7][8][9] Moreover, in positions close to the bore, where personnel may have access, measured values of switched gradient fields during clinical sequences may exceed both Directive action values (i.e., ICNIRP 1998 reference levels) and dB/dt derived limits. 10,11 Nevertheless, no standardized assessment procedures are yet available in the literature dealing with GMF signals and movements in SMF.…”
Section: Introductionmentioning
confidence: 99%